2021
DOI: 10.1215/00703370-9411326
|View full text |Cite
|
Sign up to set email alerts
|

Health of Immigrant Children: The Role of Immigrant Generation, Exogamous Family Setting, and Family Material and Social Resources

Abstract: Although the children of first-generation immigrants tend to have better health than the native population, the health advantage of the children of immigrant families deteriorates over generations. It is, however, poorly understood where on the generational health assimilation spectrum children with one immigrant and one native parent (i.e., exogamous families) lie, to what extent family resources explain health assimilation, and whether the process of assimilation varies across health conditions. We seek to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…On the other side, in the case of pediatric populations, the hypothesis of the "healthy immigrant effect" is mainly rejected. It has been shown that immigrant child health depends on contextual factors [4,27] and may actually be poorer than native children, an effect exacerbated by strict immigration policies [2][3][4][5]13]. The current study concludes that immigrant children and adolescents display poor HRQoL compared to the native group, further disproving the "healthy immigrant effect" in younger ages and instead identifying a marked health deficit.…”
Section: Discussionmentioning
confidence: 52%
“…On the other side, in the case of pediatric populations, the hypothesis of the "healthy immigrant effect" is mainly rejected. It has been shown that immigrant child health depends on contextual factors [4,27] and may actually be poorer than native children, an effect exacerbated by strict immigration policies [2][3][4][5]13]. The current study concludes that immigrant children and adolescents display poor HRQoL compared to the native group, further disproving the "healthy immigrant effect" in younger ages and instead identifying a marked health deficit.…”
Section: Discussionmentioning
confidence: 52%
“…Evidence is inconclusive about the relationship between receiving an ADHD diagnosis and immigrant background [ 10 ], but in Sweden receiving an ADHD diagnosis is associated with social disadvantage [ 12 ], and in Finland with having immigrant parents [ 13 ]. Children with one or two immigrant parents have also been reported to have a higher risk of developmental disorders related to speech and language, academic skills, or coordination [ 14 , 15 ]. Differences by immigration background in diagnoses of developmental disorders could reflect both differences in prevalence, due to exposure to various environmental risk factors or genetics, or due to differences in use of health services and in being diagnosed timely and correctly [ 10 ].…”
Section: Introductionmentioning
confidence: 99%